Don Zinzaga and Amaranta (I. Bunin and m. Chekhova) - Иванова, Наталья (Literatūra, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English] This article is devoted to a little-known life episode of the Russian writer Ivan Bunin. The correspondence between Ivan Bunin and Maria Chekhov reveals the history of his relationship with the sister of the famous writer. This article is based on archival materials, which are published only partially. For the context of this study, the correspondence of other persons (Anton Chekhov, Olga Knipper-Chekhov and others) was also involved. The letters of the “classic” writers are well-known both as a source of biographical information and as material for understanding their works; however, what also arouses interest is their correspondence with ordinary people, which allows us to study a very important part of the literary everyday life. It could be judged, on the basis of epistolary evidence, how relationships between the participants of such correspondence – people involved in literature – were formed and evolved, how their social circumstances and cultural level (among other things) influenced their personal attitudes to one another. The content, the “framing” of the letters, the lexical and syntactical features, the tone, style and the degree of frankness all completely disclose to us little-known episodes in the history of literature. Don Zinzaga ir Amaranta (I. Buninas ir M. Čechova) Straipsnyje nagrinėjami mažiau žinomi Ivano Bunino biografijos puslapiai. Ivano Bunino ir Marijos Čechovos susirašinėjime atsiskleidžia jo santykiai su kito žinomo rašytojo seserimi. Straipsnyje naudojama iki šiol dar nepilnai publikuota archyvinė medžiaga, taip pat įtraukiama ir įžymių žmonių – Аntono Čechovo, Оlgos Knipper-Čechovos – laiškai. Rašytojų „klasikų“ laiškai puikiai žinomi kaip medžiaga tiek jų biografijų tyrimams, tiek ir jų kūrybos pažinimui. Tačiau nemažiau įdomus ir „klasikų“ susirašinėjimas su „neklasikais“. Epistoliarinė medžiaga suteikia galimybė pamatyti, kaip klostėsi ir keitėsi susirašinėjančiųjų santykiai, kaip juos sąlygojo socialinė ir kultūrinė aplinka. Laiškų turinys, jų „įrėminimas“, leksikos ir sintaksės savitumas, tonas, stilius, atvirumo laipsnis – visa tai leidžia pilnai ir tiksliai atkurti mažai žinomus rusų literatūros istorijos epizodus.